Stock market and economic growth : evidence from Africa - Ferreira, Manuel Ennes (2022)
We assessed the impact of stock market development on growth in Africa. It uses annual data from a panel of 9 countries in Africa over the period 1992–2017. Panel Vector Autoregressive econometrics technique is used in data analysis. Our main findings are that stock market development has a positive effect on economic growth. Investment, human capital, and openness also positively influence economic growth in Africa. The inflation and government expenditure affect economic growth negatively. The paper also finds that using the impulse response function, economic growth reacts to the stock market for 8 years and goes back to the initial level.